The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s11230-006-9054-6
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of the Japanese species Dinosoma lophiomi Toman, 1973 (Digenea: Hemiuridae) in Lophius piscatorius (Teleostei) from the western Mediterranean

Abstract: Hemiurid worms from the stomach of the angler Lophius piscatorius off Corsica are described and considered to belong to a Japanese species, Dinosoma lophiomi Toman, 1973, which was originally described from an Indo-Pacific lophiid host. The apparent disjunctive distribution of this species and apparent differences in the terminal genitalia between the European and Japanese specimens are discussed. This is the first record of Dinosoma Manter, 1934 from the Mediterranean Sea. The validity of diagnostic features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Gibson & Bray (1986) noted that these measurements Bartoli et al (2005) and Bartoli & Gibson (2006) for authorities of taxa corresponded with those of the smallest specimens of L. fusiforme from Conger conger which they had studied (Table 3). Consequently, these authors suspected that L. grandiporum might be stunted specimens of L. fusiforme which had infected the wrong definitive host.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Gibson & Bray (1986) noted that these measurements Bartoli et al (2005) and Bartoli & Gibson (2006) for authorities of taxa corresponded with those of the smallest specimens of L. fusiforme from Conger conger which they had studied (Table 3). Consequently, these authors suspected that L. grandiporum might be stunted specimens of L. fusiforme which had infected the wrong definitive host.…”
Section: Discussionmentioning
confidence: 70%
“…All of the other digenean species have been found only in one of these three hosts (Bartoli et al, 2005; Table 4); one of these species from L. piscatorius, referred to as Dinosoma sp. by Bartoli et al (2005), has recently been identified as Dinosoma lophiomi Toman, 1973 by Bartoli & Gibson (2006).…”
Section: Additional Remarksmentioning
confidence: 99%
“… YBS Yellow Sea and Bo-hai Sea, ECS East China Sea, SCS South China Sea, TWS Taiwan Strait a Tormopsolus echenei Parukhin, 1966 is probably a synonym of Echeneidocoelium indicum Simha & Pershad, 1964 (see Bray & Cribb, 1998) b The validity of this taxon was doubted by Cribb & Bray (1999), because they draw attention to the superficial resemblance between this species and certain species of the opecoelid genus Pseudopecoeloide s Yamaguti, 1940 c Gibson (2002) considered that Proterometra brachyura Wu, Lü & Zhu, 1997, P. lamellorchis Wu, Lü & Zhu, 1997 and P. sillagae Wu, Lü & Zhu, 1997 are clearly not azygiids and are likely to be lepocreadiids d Miller & Cribb (2008) considered “ Pseudosiphoderoides xishaensis Gu & Shen, 1983 a species incertae sedis until its relationship with species in the Metadera / Siphodera group can be critically assessed” e Choudhury & Dick (1998) considered that Skrjabinopsolus sanyaensis Shen, 1990 does not belong to the Deropristidae f Pseudocoeliodidymocystis Shen, 1990 was considered a genus inquirendum by Pozdnyakov & Gibson (2008) g The full description of this species accompanied by a figure was given by Ku & Shen (1965a), but the species name was given by Shen (1990f) h Pseudofellodistomum Wang, 1987 was considered a genus incertae sedis by Bray (2008) i Elliptobursa was removed from the Monorchiidae and placed in the Haploporidae by Madhavi (2008) based mainly on its possession of “a single testis, a long external seminal vesicle, a well-developed prostatic complex, and a long hermaphroditic duct wrongly interpreted as a cirrus” j Bray (1990) considered that Ectenurus carangis Gu & Shen, 1978 and E. megalaspis Gu & Shen, 1978 may be synonymous k This synonymy follows Gibson & Bray (1986) l Bray (1991) considered that Lecithochirium miichthydis Wang, 1982, L. muraenesocis Wang, 1982 and L. scomberomori Wang, 1982 are probably members of other genera m Léon-Règagnon et al (1996) and Bray & Cribb (2002) considered that Opisthadena fujianensis Tang, Shi & Guan, 1983 and O. marina Tang, Shi & Cao, 1983 are species inquirendae n Bartoli & Gibson (2006) considered that “the description of this species is not detailed enough to confirm its genetic allocation” o This synonymy follows Manter & Pritchard (1960) and Bray et al (1993) p This synonymy follows Gibson (2002) q This synonymy follows Bray & Cribb (1997) r Bray & Gibson (1995) treated Lepidapedon sphyraenae Shen, 1990 as incertae sedis s Bray & Nahhas (1998) considered that Bianium lianyungangense Shen, 1990 may be close to Lepocreadioides Yamaguti, 1936 based on the position of the genital pore, the lobation of the ovary and the host t Bray et al (1997) considered that Intusatrium crassum Wang, 1987 is a species inquirenda u Bray & Cribb (1998) considered that “ L. pagrosomi Wang, 1982 probably does not belong in Lepocreadioides , as it has an entire ovary and the genital pore, although marginal, is more posterior than is usual for the genus. The figure gives no evidence of tegumental spines or an external seminal vesicle, indicating that the species may not belong in the Lepocreadiidae”…”
Section: Methodsmentioning
confidence: 86%
“…n Bartoli & Gibson (2006) considered that “the description of this species is not detailed enough to confirm its genetic allocation”…”
Section: Methodsmentioning
confidence: 99%
“…We found neither nematode nor any other parasite groups except digenean parasites in L. piscatorius. In light of the literature, it is obvious that a lot of parasite taxa were found in L. piscatorius of various seas of the world (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) (Table 4). Consequently, parasites of the angler fish of Turkish seas must be comprehensively studied.…”
Section: Resultsmentioning
confidence: 99%